Identifying Probable Slip Surface in Wanurejo, Borobudur District, By Subsurface Analysis Utilizing the Dipole-Dipole Configuration of Resistivity Method - Nurul Dzakiya; Robertus Belardo Laksmana; Radhitya Adzan Hidayah (Journal of Applied Geospatial Information, 2023)
Research has been carried out on the existence of slip surfaces in Wanurejo, Borobudur District, Magelang Regency, Central Java. The location of the slip surface is identified using the resistivity method of the dipole-dipole configuration. This research was conducted at a relatively flat measurement location and at an altitude of around 95–105 meters above sea level. Measurements were made on 6 different lines with a length of track 1 of 250 m. The results of data processing indicate that the layer that acts as a slip surface is a layer of clay. The clay layer has a resistivity value ranging from 15 to 35 ohm.m, which is relatively thin, so it has the potential to become a slip surface because it is located between two rocks that have a significant resistivity contrast: compact andesite rock and water-saturated sandstone. If the water-saturated sandstone layer is no longer able to withstand the weight above it, the surrounding andesite rocks will easily slip. This is also reinforced by the presence of a layer of clay that is slippery, so the potential for landslides or slipping is greater.